A management guide to logistics engineering - Beal, K. (London Institution of Production Engineers, 1989)
This guide will prove a great help to businesses in providing the pratical advice that will enable them to master the art of logistics so it can be used to their best business advantage.
Electronic reproduction.
Keywords: Systems engineering; Logistics; Electronic books